2014
DOI: 10.1136/bmjopen-2013-003697
|View full text |Cite
|
Sign up to set email alerts
|

The assessment and impact of sarcopenia in lung cancer: a systematic literature review

Abstract: ObjectivesThere is growing awareness of the relationship between sarcopenia (loss of muscle mass and function), and outcomes in cancer, making it a potential target for future therapies. In order to inform future research and practice, we undertook a systematic review of factors associated with loss of muscle mass, and the relationship between muscle function and muscle mass in lung cancer, a common condition associated with poor outcomes.DesignWe conducted a computerised systematic literature search on five d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
88
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 92 publications
1
88
0
2
Order By: Relevance
“…Several studies have reported that sarcopenia was associated with poor prognosis in lung cancer, but most of these included patients with advanced stage cancer . According to a rare report about sarcopenia in stage I NSCLC patients, sarcopenia was associated with poor prognosis in men but was not associated with postoperative complications .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that sarcopenia was associated with poor prognosis in lung cancer, but most of these included patients with advanced stage cancer . According to a rare report about sarcopenia in stage I NSCLC patients, sarcopenia was associated with poor prognosis in men but was not associated with postoperative complications .…”
Section: Discussionmentioning
confidence: 99%
“…In multiple surgical populations, such as vascular, gastrointestinal, urological, gynaecological, and transplantation surgery, the association between low skeletal muscle mass and an increased risk of post operative complications, recurrent disease, or impaired survival has been shown. Low skeletal muscle mass is also related to discharge destination in elderly trauma patients, associated with an increased risk of dose‐limiting chemotherapy toxicity and with morbidity and mortality in various oncologic populations, such as lung cancer and melanoma patients . Furthermore, CT‐assessed visceral obesity is associated with worse short‐term and long‐term outcome in distinct patient populations undergoing surgery .…”
Section: Discussionmentioning
confidence: 99%
“…Low skeletal muscle mass is also related to discharge destination in elderly Software programmes for body composition measurements on CT trauma patients, 45 associated with an increased risk of doselimiting chemotherapy toxicity 17,24,25,46 and with morbidity and mortality in various oncologic populations, such as lung cancer and melanoma patients. 47,48 Furthermore, CT-assessed visceral obesity is associated with worse short-term and long-term outcome in distinct patient populations undergoing surgery. 30 Various software programmes have been used to measure body composition in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with numerous negative outcomes, including an impaired stress response, frailty, functional impairment, lower quality of life and decreased overall survival [34][35][36][37]. As such, acute sarcopenia, could then explain, at least in part, the dramatic drop in quality of life experienced by even the most functional patients at baseline who undergo CTRT for HNSCC [38].…”
Section: Main Textmentioning
confidence: 99%